Should the Optimal Adjuvant Treatment for Patients With Early-Stage Endometrial Cancer With High-Intermediate Risk Factors Depend on Tumor Grade?. Issue 8 (1st October 2015) - Lan, Chunyan; Huang, Xin; Huang, Qidan; Wang, Yin; Gu, Haifeng; Li, Yong; Liu, Jihong
Abstract : Objectives: To explore whether the optimal adjuvant treatments for patients with early-stage endometrial cancer with high-intermediate risk (HIR) factors should depend on tumor grade. Methods: A retrospective analysis of patients with HIR endometrial cancer from 1999 to 2012 was conducted. The adjuvant treatments and survival were evaluated. Results: A total of 129 patients with HIR were identified, of which 71 had grade 1–2 tumor and 58 had grade 3 tumor. The adjuvant treatment chosen differed significantly between patients with grade 1–2 and grade 3 tumors ( P < 0.001). Most of the patients (76.1%) with grade 1–2 tumors received no adjuvant treatment; however, chemotherapy alone was the most frequent (75.9%) adjuvant treatment for patients with grade 3 tumors. In the grade 1–2 group, no significant differences in the 5-year progression-free survival (94.1% vs 96.3%; P = 0.857) and overall survival (OS) rates (94.1% vs 98.1%; P = 0.401), respectively, were observed between patients who received adjuvant treatment (radiation and chemotherapy with or without radiation) and those who did not. For grade 3 disease, patients undergoing adjuvant chemotherapy alone had a favorable outcome with the 5-year progression-free survival rate of 84.4% and the OS rate of 95.5%. Conclusion: It is logical to speculate that surgery followed by observation might be sufficient for patients with HIR with grade 1–2 tumor. Further prospective trials are required to confirm the issue owing to the limited number of this population. More studies are warranted to clarify the feasibility and efficacy of adjuvant chemotherapy alone in patients with HIR with grade 3 tumor.